Studies on the Mechanical, Morphological and Electrical Properties of Highly Dispersible Graphene Oxide Reinforced Polypyrrole and Polyvinylalcohol Blend Composites. (2018) - Deshmukh, Kalim; Basheer Ahamed, M.; Sankaran, Sowmya; Khadheer Pasha, S.K.; Kumar Sadasivuni, Kishor; Ponnamma, Deepalekshmi; Al-Ali AlMaadeed, Mariam
Abstract: In the present study, water soluble polypyrrole (WPPy)/polyvinyl alcohol (PVA)/graphene oxide (GO) composite films were prepared via colloidal blending method at different GO loadings varying from 0 – 3 wt%. The dispersion of GO in the WPPy/PVA blend matrix was examined using polarized optical microscopy (POM) and scanning electron microscopy (SEM). It was observed that the tensile strength of the composite film was changed considerably due to the incorporation of GO in the WPPy/PVA blend. The electrical properties, viz. impedance (Z), phase angle (θ) and quality factor (Q), were evaluated using the precision impedance analyser in the wide frequency (50 Hz to 20 MHz) and temperature (40°C to 150°C) ranges. The impedance was notably increased from 7.8 x 10 5 Ω (50 Hz, 70°C) for the WPPy/PVA blend to 1.37 x 10 7 Ω (50 Hz, 40°C) for the WPPy/PVA/GO composites with 3 wt% GO loading. On the other hand, the phase angle was gradually increased from 99.7 o (20 MHz, 140°C) for WPPy/PVA blend to 199.8 o (20 MHz, 80°C) for WPPy/PVA/GO composites with 3 wt% GO loading. Furthermore, the Q factor also increased from 14. 9 (10 MHz, 120°C) for WPPy/PVA blend to 108.8 (10 MHz, 150°C) for WPPy/PVA/GO composites with 3 wt% GO loading. These composites can be a promising material for electronic applications.